Associations Of Electronic Service Quality And Promotion With Customer Satisfaction Among Shopee Users In Bandung City - Muhammad Raihan Fahrezi; Arus Reka Prasetia (Journal of Business and Management Inaba, 2026)
Prior Shopee studies provide inconsistent evidence on whether promotion remains associated with customer satisfaction when electronic service quality is considered simultaneously, and several have focused on narrowly defined respondent groups. This study reassesses these relationships among Shopee users in Bandung City through a quantitative cross-sectional survey. Data were collected in 2025 from 97 eligible respondents using non-probability incidental sampling and a 30-item context-adapted questionnaire administered through Google Forms. The data were analyzed using descriptive statistics, item-to-to-to-total correlations, Cronbach’s Alpha, regression diagnostics, multiple linear regression, and HC3 heteroscedasticity-robust inference. Electronic service quality and promotion were both positively associated with customer satisfaction. Under HC3 robust inference, electronic service quality was positively associated with customer satisfaction (B = 0.477, p < 0.001), as was promotion (B = 0.446, p < 0.001), while promotion produced B = 0.446, p < 0.001. The model explained 75.8 percent of the observed variation in customer satisfaction, with R² = 0.758 and adjusted R² = 0.753. Because the two unstandardized coefficients were numerically close and were not formally compared, neither predictor was interpreted as meaningfully stronger. The study contributes a contemporary robustness-oriented replication and contextual extension of an established Shopee model using 2025 data and an operational specification that incorporates trust and transaction security within electronic service quality. Given the cross-sectional, single-source design, the findings indicate associations rather than causal effects and should be interpreted with caution.